ASPECTOS TÉCNICOS E CUSTOS NA DETERMINAÇÃO DA DENSIDADE DE ESTRADAS EM PLANTIOS FLORESTAIS - Faria, Felipe Nascimento de (2020)
The road density inadequate cause increased production costs, loss of planting area and environmental impacts e the analysis of optimal road density considering terrain conditions, forest gender, timber storage capacity and number of machine can support this. The general object of this study was to determine current road density, optimal road density and operational density in different terrain conditions and forest gender to full tree harvester system. The method applied was the indirect, throught the minimization of total costs, which contemplated the sum of road construction cost, road maintenance cost, skidding cost, loss of planting area cost and impact cost of road. It was create a restriction of timber storage capacity (CME), and was analyzed from the forest road fee utilization and theoretical stock capacity. At the definition of DOP, was considered the number of machines to attend annual production demand in different terrain conditions, added cost of increasing machines in total cost. The results showed that the slopping areas have the highest cost of timber skidding and road construction and the cost of loss of planting area were higher in flats areas. All scenarios in the DOE the CME was less than the estimate volume of production, while in DOP, in all scenarios, the CME was bigger then, except as sloping eucalyptus areas. In general, DE, DOE and DOP were higher in the most sloping areas and DOE and DOP were higher than DE in all scenarios, except sloping eucalyptus areas. In the flat areas of eucalyptus the current road density was 85 m ha-1 , the DOE of 38 m ha-1 and the DOP of 74 m ha-1 . In the flat areas of eucalyptus the DE was of 102 m ha-1 , the DOE 44 m ha-1 and the DOP of 123 m ha-1 . In the flat areas of pine DE was of 126 m ha-1 , the DOE of 53 m ha1 and the DOP of 92 m ha-1 . In the sloping areas of pine DE was of 180 m ha-1 , the DOE of 65 m ha-1 and the DOP of 123 m ha-1 . The road planning must considered terrain conditions and forest gender, because both impact the road density, as the CME and DOP, that adapt the planning to local conditions and situations and make it possible to verify the feasibility of implementing the DOE and the real potential for gains in operating costs.